Penguatan Literasi Digital Online dalam Meningkatkan pemahaman Siswa terhadap Wawasan Nusantara: Studi Kasus Kelas X SMA Negeri 1 Percut SEI Tuan - Siti Fatimah Sari Ritonga; Ovi Oktavia K Sihombing; Irenita Perangin Angin; Pretty Grace Banjarnahor; Juli Ramayani; Parlaungan Gabriel Siahaan; Novridah Reanti Purba (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Right now computerized education is vital in the time of Indonesian culture, particularly for understudies or understudies. Computerized education is an individual's capacity to utilize web network-based specialized devices to get, add and pass on data. In this examination, the creator will dissect the capacity of understudies at SMA Negeri 1 Percut Sei Tuan in executing on the web computerized education to widen their understanding into the archipelago. This exploration utilizes unmistakable quantitative strategies, specifically research completed by meetings and finishing up polls. This examination was completed by finishing up a survey with one class X comprising of 30 understudies and talking 1 instructor of citizenship schooling subjects at SMA Negeri 1 Percut Sei Tuan. This examination expects to decide the impact of computerized proficiency in expanding understudies' knowledge into the Indonesian archipelago in citizenship training learning. Expanding the comprehension of public knowledge in understudies is exceptionally powerful in expanding the sensation of affection for the nation to keep up with the respectability of the country.